A New Synergistic Approach to Studying Drag Reduction of Rigid Polymer and Microbubbles in Turbulent Flow - Oluwasoga, Akindoyo Edward; Abdulbari, Hayder A.; Olaotan, Ogunleye Olaide (Universiti Malaysia Pahang, 2016)
Drag has been a challenge encountered in liquid transportation of liquids. A universal means of reduction has however, not been implemented. Most efforts made to study its working mechanism and finding best environmental friendly approaches have been major setback. Mostly, materials investigated to militate these challenges are either less effective or harmful to the environment. In this work, an environmental friendly approach which entails bubble injection into rigid polymer (Xanthan gum) was investigated. The materials were tested individually and as complex. 51%, 56% and 62% drag reduction were obtained for 700ppm of the xanthan gum alone in the RDA, 700ppm in the pipe and 700ppm of xanthan gum with microbubbles pipe respectively. Despite the fact that the individual additives were able to reduce drag, their complex mixture showed better performance. The performance of the complex could be attributed a synergy which occurs between these additives, thus suggested a new working mechanism of the duo. Based on the combination of these additives, it could be concluded that there is an extra drag reduction when they are combined than the individual additive. Aside this, there is a synergistic relationship in their drag reduction mechanism.